ANALISA KADMIUM (Cd) PADA AIR SUMUR DI SEKITAR PERSAWAHAN DI DESA MOMPANG KECAMATAN PADANGSIDIMPUAN ANGKOLA JULU KOTA PADANGSIDIMNPUAN TAHUN 2013 - Putri Ramadhani Irsan; wirsal hasan; indra chahaya (Lingkungan dan Kesehatan Kerja, 2014)
Water is essential for life, but in many cases the water used was not always in accordance with the requirements of health because of the pollution that occurs in water, especially groundwater contaminated by heavy metal pollutants cadmium (Cd) due to excessive use of fertilizers in farming. The objective of the research is to determine the content of cadmium (Cd) in the wells water and construction of the wells around the rice fields in Desa Mompang Kecamatan Padangsidimpuan Angkola Julu Kota Padangsidimpuan. This research used a descriptive survey design to describe the content of cadmium (Cd) in wells water around the rice fields in qualitative and quantitative results obtained from laboratory tests based Permenkes RI No. 416/MEN/KES/IX/1990 about terms and Water Quality Monitoring, and used the Hit Chain. Sample was selected by purposive sampling about 30 wells. The results showed that all of the well was cadmium (Cd) contented. There as many as 17 wells (56.7%) did not qualified. Quantitatively in the lowest well water contained in the well 24 was 0.00276 mg/l and the highest content found in wells 4 was 0.00684 mg/l. Water conditions and wells construction were in the intermediate level of contamination of cadmium (Cd) with 60,0% Researchers had assumed that the entry of cadmium (Cd) into the wells public in Desa Mompang tanded to increase in wells within <10 meters from the rice fields to obtain quite high runoff pollution burden derived from the remnants of phosphate fertilizers that settled and accumulated on the ground then influenced by the construction of dug wells were unstandarized made perfect pollutants into wells. It was recommended to the farmers in Desa Mompang Kecamatan Padangsidimpuan Angkola Julu Kota Padangsidimpuan to use fertilizer according to the recommended dosage so it didn’t impact on the environment, especially water well contamination. Keywords: Water Wells, Cadmium (Cd), the Well Construction